Prevalence and Risk Factors of Iron-Deficiency Anemia in Children Under 5 Years in Urban vs. Rural Settings - Amna Minhas, Umm E Habiba, Sadia Malik, Waleed Yousaf, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Iron-deficiency anemia (IDA) is a leading cause of childhood morbidity, especially in low- and middle-income countries. Children under five years are particularly vulnerable due to rapid growth and increased iron demands. Objective: To assess the prevalence of iron-deficiency anemia among children under five years of age and to compare associated risk factors between urban and rural settings. Methods: This cross-sectional comparative study was conducted at Mayo Hospital Lahore from January 2023 to July 2023. The target population included children aged 6 to 59 months who were residents of either urban or rural areas and presented to the selected healthcare centers for routine medical services. Children were eligible if they were apparently healthy or had minor illnesses that did not interfere with hemoglobin status. A total of 455 children were enrolled in the study, comprising 230 children from urban settings and 225 from rural settings, selected through non-probability consecutive sampling. Results: The overall prevalence of IDA was 52.5%, with significantly higher rates in rural children (62.7%) compared to urban children (42.6%) (p < 0.001). IDA was more prevalent among children aged 6–24 months (66.4%), those with low maternal education (71.3%), low dietary diversity (68.2%), and recent gastrointestinal infections (63.9%). Iron supplementation (29.4% prevalence) and exclusive breastfeeding (44.3%) were protective factors. Multivariate logistic regression identified rural residence (AOR: 2.44), poor dietary diversity (AOR: 2.89), low maternal education (AOR: 2.21), and recent GI infection (AOR: 1.67) as significant risk factors. Iron supplementation (AOR: 0.39) and exclusive breastfeeding (AOR: 0.63) were independently protective. Conclusion: Iron-deficiency anemia remains alarmingly prevalent, particularly among rural children under five. Socioeconomic disparities, poor dietary practices, and limited healthcare access contribute to this burden. . Keywords: IDA, Children, Urban, Rural, Diet, Education, Supplements, Breastfeeding